Monitoring soil resilience via the dynamic changes of selected physicochemical properties of soil in a tropical rehabilitated forest - Md Taha, Muhamad Khairulamiin; Mohamad, Azham; Che Sulaiman, Intan Soraya; Md Isa, Isharudin; Khairuddin, Mohd Nizar (Chaoyang University of Technology, 2022)
Recovery of soil organic matter and mineral nutrient cycling are critical to the success of rehabilitation process of replanted forest. We investigated the dynamic changes in soil of selected physicochemical properties including organic carbon (C), nitrogen (N), phosphorus (P) and sulphur (S) of replanted forest rehabilitation that had been previously disturbed by anthropogenic activities. Soil samples were collected from the rehabilitated forest of three ages stands (3-, 12- and 23-years old) while samples from adjacent secondary forest was collected for comparison. Altogether, 36 samples were taken randomly with a soil auger at depths of 0-20 cm from a plot of 20 × 20 m2 at each site. Soils were analyzed for pH, bulk density, C, N, P and S. The data obtained were statistically analyzed using ANOVA with Tukey’s test performed by SAS 9.2 at P ≤ 0.05. Results showed that total C, N, P, C/N ratio and C/S ratio increased with age of rehabilitated forest except for pH, S and C/P ratio. Forest rehabilitation by planting indigenous tree species has shown a potential of recovery, but further investigation into the process control of the dynamic changes of soil physicochemical properties, particularly in the event of further ecosystem disturbance is needed.